Producción de xilitol por Candida guilliermondii a partir de fermentación de residuos de palma de aceite (2016)
The dilute-acid hydrolysis of oil palm empty fruit bunch produces fermentable sugars such as xylose, main carbon source for xylitol production by Candida guilliermondii. The influence of different culture media and fermentation conditions were evaluated on the production of xylitol from oil palm empty fruit bunch using C guilliermondii. The acid hydrolyzated oil palm empty fruit bunch supplemented with 4g yeast extract/L, 3g (NH4)2SO4/L, 0.5g MgSO4.7H2O/L y 0.1g CaCl2.2H2O/L, was the best culture medium for the yeast growth in submerged culture because it had the highest values, statistically significant, of the specific growth rate 0.12h-1 and biomass production 5.5g/L (p<0,05). The suitable fermentation conditions were obtained with hydrolyzated oil palm empty fruit bunch supplemented at pH 5.5, initial xylose concentration of 17g/L and an inoculum of 3g/L. Microaerobic condition is an important factor on the fermentation process, with a volume of 40mL in a flask of 100mL, that produces the highest concentrations of xylitol (6.7g/L) (p<0,05).